Perawatan Saluran Akar dengan teknik Step Back pada Kasus Pulpitis Irreversible dengan Jaringan Apikal Normal Gigi Insisif Mandibula - Pratiwi, Amatul Firdaustia; Fatriadi, Fajar (Journal of Syiah Kuala Dentistry Society, 2024)
Introduction: Caries is a bacterial infection of the teeth that can attack the enamel, dentin, and pulp. Caries extending to the pulp can result in irreversible pulpitis, where root canal treatment is indicated so the tooth can return functionally and aesthetically. Case report: A 50-year-old woman came with chief complaints of cavities in her lower front teeth. From subjective, objective, and radiographic examination, tooth 31 was diagnosed with irreversible pulpitis with normal apical tissue, and a root canal treatment was planned. In the next visit, the root canal treatment was carried out using the step-back technique starting from IAF K-File #10 and MAF K-File #25 with a working length of 22.5 mm. The final K-File used was K-File #40, with a working length of 19.5 mm. Root canal treatment on tooth 31 was carried out in 10 visits. After radiographic evaluation subjective and objective examination, the root canal treatment was completed, and a post-crown restoration was planned as a follow-up. Conclusion: Root canal treatment in 10 visits on tooth 31, which was diagnosed with irreversible pulpitis with normal apical tissue, carried out using the step-back technique in this case, showed clinical and radiological success.